PERBEDAAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH RIGHT ISSUE STUDI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2019-2021 - Hamdana, Hamdana; Amelia Saragih, Dothy; Harni, Harni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This study aims to investigate the potential differences in the financial performance of companies before and after conducting rights issues listed on the Indonesia Stock Exchange. The financial performance of these companies is evaluated using various financial ratios, including the current ratio (CR), debt to equity ratio (DER), return on assets (ROA), and return on equity (ROE). This study employed a quantitative method, utilizing data obtained from the Indonesia Stock Exchange spanning the years 2018 to 2021. Sampling was conducted using a purposive sampling method, involving a total of 26 companies that carried out rights issues. The statistical test used in this study was the Wilcoxon signed rank test. The results of this study indicate that the which Wilcoxon signed rank reveals a significant difference in the current ratio and debt to equity ratio before and after the rights issue, whereas no significant difference was observed in the return on assets and return on equity variables before and after the rights issue.